20 How does BMI influence heart failure programme outcomes?-Testing the obesity paradox. (30th September 2020) - Byrne, L; Wheen, P; Murray, P; Minelli, C; O'Callaghan, D; Daly, C
Abstract : Introduction: A complex physiological relationship exists between obesity and heart failure (HF) with many large-scale studies reporting a paradoxical improvement in cardiovascular (CV) mortality in obese patients. Many of these studies retrospectively analyzed RCT trials not designed to investigate the role of obesity in HF outcomes. We aim to establish if different outcomes exist after HF programme completion based on body mass index (BMI). Methods: A multi-centre retrospective observational study was carried out in 3 hospitals' HF clinics. New patients referred to each HF service over a 12 month period were reviewed, or in a 24 month period in one centre, with a left ventricular ejection fraction (LVEF) < 50% were eligible for inclusion. Patient records were obtained to collect patient demographics, New York Heart Association (NYHA) class symptoms, NT-proBNP, LVEF and medications at initial referral and at programme completion. Hospitalisation rate for HF and mortality was also noted. Patient characteristics and outcomes were compared between non-obese (BMI < 29.9) and obese (BMI >30). Results: 93 patients were included for analysis and a follow up of (mean (±SD) 16.5 months (±8.8) was obtained. 63 (67.7%) had a BMI <29.9 and 30 (32.3%) had a BMI >30. Obese patients were more likely to be male (p=0.03), diabetic (p=0.05) and have hypertension (p<0.001). No significant differences in medical or device therapy was noted between groups. Obese patients had a greater improvement in their LVEF following programme completion (10.5% (±11.7) versus 7.95% (±10.7)), although this did not reach statistical significance (p=0.34). Obese patients had significantly lower NT-pro BNP levels at HF programme completion ((median(IQR)) (546.4 () versus 962 (), P=0.02) however this improvement was not significantly greater than that seen in non-obese patients (p=0.8). Although no difference in mortality was noted between the groups (8 (12.7%) versus 3 (10%), p=0.73), obese patients had significantly fewer HF hospitalisations than the non-obese group (0.33 (±0.74) versus 0.04 (±0.2), p=0.005). Conclusion: Despite higher rates of diabetes and hypertension in obese patients, there was no significant difference in mortality, LVEF improvement and NT-proBNP improvement following HF programme completion between the 2 groups. However, obese patients had significantly less HF hospitalisations during the study period than non-obese patients.